Figurative Repatriation First Nations ‘Artist-Warriors’ Recover, Reclaim, and Return Cultural Property through Self-Definition - Kramer, Jennifer (Journal of Material Culture, 2004)
This article begins with an analysis of the problems of ‘physical repatriation’, as I review the case of the return of a First Nations mask to its community of origin. First Nations struggle to fit their concepts of ownership into western ones, where objects are viewed as alienable. As an alternative, the art of John Powell and Marianne Nicolson depicts a ‘figurative repatriation’ that does not rely on either the courts or museums to recognize legal or moral ownership. I argue that these contemporary artworks are social agents, which bring First Nations cultural objects home by staking out territory within museums. These ‘artist warriors’ forcibly recover (both literally and metaphorically) First Nations objects on display in foreign settings and reinscribe meaning at the level of the personal and the communal. They make objectified assertions of native identity that reclaim the right to self-definition. Moreover, these claims are made all the more powerful through their conscious location within an oppositional discourse framed by the Canadian western art world.
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice autochtone; _Nettoyé